An unusual presentation of a severely calcified subserous leiomyoma in a postmenopausal woman: a case report - Samal, Sunil Kumar; Rathod, Setu; Rani, Reddi; Anandraj, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report a case of a 58-year-old postmenopausal woman presented with mass descending per vaginum with lower abdominal discomfort for last one year. Examination revealed second stage utero-vaginal prolapse according to Pelvic organ prolapsed quantification (POP-Q) system with a hard mobile mass of size 6x6 cm in pouch of Douglas. After workup, it was diagnosed as posterior subserosal calcified leiomyoma of FIGO (International Federation of Gynaecology and Obstetrics) class 6. Vaginal hysterectomy with pelvic floor repair was done and histopathological examination confirmed a calcified leiomyoma.